2002
DOI: 10.1002/ana.10161
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's neurofibrillary pathology and the spectrum of cognitive function: Findings from the Nun Study

Abstract: The development of interventions designed to delay the onset of dementia highlights the need to determine the neuropathologic characteristics of individuals whose cognitive function ranges from intact to demented, including those with mild cognitive impairments. We used the Braak method of staging Alzheimer's disease pathology in 130 women ages 76-102 years who were participants in the Nun Study, a longitudinal study of aging and Alzheimer's disease. All participants had complete autopsy data and were free fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
243
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(266 citation statements)
references
References 58 publications
18
243
1
4
Order By: Relevance
“…Furthermore, the spatiotemporal development of NFT in AD is correlated to the clinical severity of the disease and the cognitive decline of the patients [136]. Initial NFT formation is found in the transentorhinal region in the temporal lobe.…”
Section: Accumulation Of Ndna Damage or Neuron Loss: Implications Formentioning
confidence: 99%
“…Furthermore, the spatiotemporal development of NFT in AD is correlated to the clinical severity of the disease and the cognitive decline of the patients [136]. Initial NFT formation is found in the transentorhinal region in the temporal lobe.…”
Section: Accumulation Of Ndna Damage or Neuron Loss: Implications Formentioning
confidence: 99%
“…Recent functional evidence suggests that Aβ initiates the AD changes, but pathological tau protein causes neurodegeneration and better correlates with the clinical manifestation of the disease (Arriagada et al ., 1992; Riley et al ., 2002). While we know that NFTs are mainly composed of abnormally hyperphosphorylated tau that aggregates into paired helical filaments and straight filaments, the mechanisms leading to the abnormal hyperphosphorylation of tau in the brain of AD patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a triple transgenic mouse model, intraneuronal accumulation of Aβ was shown to be associated with deficits in synaptic plasticity before AD lesions developed. [33] Conversely, other autopsy studies [11,26,38] reported NFT to be the dominant lesion in AD and mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%